Corneal Sensitivity Following Lacrimal Gland Excision in the Rat - Meng, Ian D. (Invest Ophthalmol Vis Sci, 2015)
PURPOSE. Dry eye disease (DED) produces ocular pain and irritation, yet a detailed characterization of ocular sensitivity in a preclinical model of DED is lacking. The aim of the present study was to assess nociceptive behaviors in an aqueous tear deficiency model of DED in the rat. METHODS. Spontaneous blinking, corneal mechanical thresholds, and eye wipe behaviors elicited by hypertonic saline (5.0 M) were examined over a period of 8 weeks following the unilateral excision of either the exorbital lacrimal gland or of the exorbital and infraorbital lacrimal glands, and in sham surgery controls. The effect of topical proparacaine on spontaneous blinking and of systemic morphine (0.5–3.0 mg/kg, subcutaneous [SC]) on spontaneous blinking and eye wipe responses were also examined. RESULTS. Lacrimal gland excision resulted in mechanical hypersensitivity and an increase in spontaneous blinking in the ipsilateral eye over an 8-week period that was more pronounced after infra- and exorbital gland excision. The time spent eye wiping was also enhanced in response to hypertonic saline (5.0 M) at both 1- and 8-week time-points, but only in infra- and exorbital gland excised animals. Morphine attenuated spontaneous blinking, and the response to hypertonic saline in dry eye animals and topical proparacaine application reduced spontaneous blinking down to control levels. CONCLUSIONS. These results indicate that aqueous tear deficiency produces hypersensitivity in the rat cornea. In addition, the increase in spontaneous blinks and their reduction by morphine and topical anesthesia indicate the presence of persistent irritation elicited by the activation of corneal nociceptors.